Comparison Between Ultrasound (US) And Fine Needle Aspiration (FNA) Findings In Axillary Lymphadenopathy (LAP) “Classification” - Nabee, Hana Kamal; Younis, Saeed Nadhim (Adolescência e Saúde, 2026)
Background: Axillary lymphadenopathy is one of the most common pathologies encountered in the axillary region, which is defined as an abnormality in the size and characteristics of the lymph node. The imaging modality of choice for evaluation of the axilla is ultrasound. When suspicious lymph nodes are identified on ultrasound, fine-needle aspiration or core-needle biopsy typically follows, both to establish a histological diagnosis and to guide further management. Objective: The objective of the study is to know whether the suspicious lymph nodes in ultrasound are in fact pathologic or not. Methodology: present study was prospective observational comparative study implemented in Rizgary teaching hospital and Erbil Breast center in duration of two years from 1st march 2023 to 1st March 2025 on sample of 120 patients with axillary lymphadenopathy, FNA was taken from the ultrasonographically suspicious lymph nodes and the results have been compared. Results: The accuracy indicators of ultrasonography compared with the fine needle aspirate were as follows: sensitivity (64.5%), specificity (67.2%), predictive value of a positive test (67.8%), predictive value of a negative test (67.2%), The malignancy rate among patients with round lymph nodes (77.8%) was significantly higher (p < 0.001) than that in patients with oval lymph nodes (36%). When the hilum was not preserved, the malignancy rate was 68.8%, compared to 32.1% when the hilum was preserved (p < 0.001). Malignant changes were observed in patients with hypoechoic lymph nodes, compared to 31.1% in patients with normal echogenicity (p < 0.001). Conclusion: No single ultrasound sign is absolutely accurate in diagnosing peripheral lymph node malignancy. The association of signs produces a highly suggestive appearance in most cases.